STUDI PERBANDINGAN MODEL PERHITUNGAN LABA ANTARA PEGADAIAN SYARIAH DENGAN PEGADAIAN KONVENSIONAL - Bahkamil Bahkamil (AkMen JURNAL ILMIAH, 2013)
Object of this study was to compare the profit model of Islamic mortgages and conventional mortgages. Through a qualitative description of the research method of this study illustrate the calculation system between Shariah and Conventional mortgages. The purpose of this study to determine how the Shariah and Conventional mortgages for a profit with each calculation system. Then, through this study is expected to provide information to the public in a decision and choose a mortgage. In conclusion, between Shariah and Conventional mortgages, Sharia is not using the rental income to get a loan and do not use Sharia Pawn fiduciary practices to gain profit.